Cyberloafing, nomophobia, and addiction among college students - Fuady, Ikhsan; Widyowati, Weny; Sutarjo, Moch Armien Syifaa (Institute of Computer Science (IOCS), 2025)
The development of communication technology has social, psychological and other social impacts. The presence of smartphones has a serious impact on cyberloafing behavior, nomophobia and addiction among students. This study aims to determine a model that describes the relationship between nomophobia, cyberloafing and addiction among college students. This research is designed as a quantitative research with a survey approach. The survey was conducted on 123 students in West Java by convenience sampling. Data analysis using Structural equation modeling test with lisrel 8.50. The results showed that the higher the anxiety of students if without a smartphone will increase cyberloafing behavior among students. In addition, this study shows that the higher the anxiety without a smartphone will strengthen the level of addiction among students. Cyberloafing behavior has no significant effect on increasing addiction to smartphones among students. Suggestions from these findings, the importance of self-control of nomophobia students to be able to reduce addiction to smartphones and also cyberloafing behavior that causes low effectiveness of student achievement.